2016
DOI: 10.1007/978-3-319-46095-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Embryonic Cleavage Pattern Determination

Abstract: The pattern of the earliest cell divisions in a vertebrate embryo lays the groundwork for later developmental events such as gastrulation, organogenesis, and overall body plan establishment. Understanding these early cleavage patterns and the mechanisms that create them is thus crucial for the study of vertebrate development. This chapter describes the early cleavage stages for species representing ray-finned fish, amphibians, birds, reptiles, mammals, and proto-vertebrate ascidians and summarizes current unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 236 publications
(343 reference statements)
1
21
0
Order By: Relevance
“…During early cleavage divisions, vegetal or yolk-rich blastomeres are created larger than animal blastomeres. Cephalopods, birds, reptiles and fish embryos illustrate the extreme case for the effect of yolk, whereby cell division occurs in a meroblastic fashion atop a mass of non-dividing yolk (Hasley et al, 2017). Hertwig tested the effect of yolk on cell division by centrifuging Xenopus eggs thus concentrating the yolk to one side of the egg.…”
Section: Effect Of Yolk On Ucdmentioning
confidence: 99%
“…During early cleavage divisions, vegetal or yolk-rich blastomeres are created larger than animal blastomeres. Cephalopods, birds, reptiles and fish embryos illustrate the extreme case for the effect of yolk, whereby cell division occurs in a meroblastic fashion atop a mass of non-dividing yolk (Hasley et al, 2017). Hertwig tested the effect of yolk on cell division by centrifuging Xenopus eggs thus concentrating the yolk to one side of the egg.…”
Section: Effect Of Yolk On Ucdmentioning
confidence: 99%
“…The eukaryotic cytoskeleton represents a dynamic network of protein filaments and tubules that has been extensively studied in a variety of model systems. In addition to basic cellular functions, including nuclear division, cytokinesis, organelle positioning, membrane trafficking and cell expansion, the cytoskeleton plays an important role in processes such as polar cell growth, cell division plane positioning, or cell to cell communication, which are essential for proper morphogenesis and thus the development of multicellular bodies in both metazoans [1] and plants [2]. This dynamic network relies on a large ensemble of cytoskeleton-associated proteins controlling organization, remodeling, and crosstalk of cytoskeletal systems, as well as coordination of the cytoskeleton with cell membranes and organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental work in echinoderms, fish, and frog embryos has suggested that division plane specification in large eggs and blastomeres is instructed from interphase/anaphase microtubule (MT) asters which fill the large cellular volume, and probe cell shape through length-dependent MT forces [6,7]. This mechanism aligns the division axis with the cell shape long axis, and has been proposed to serve as a default cue guiding division plane orientation and position in early embryos [14,15]. Given the presence of asymmetric divisions in some blastomeres of many embryos, cell shape effect may be overridden or biased by additional cues such as vegetal polarity domains in echinoderms or by yolk layers in fish and amphibians, which alter the distribution of MT forces around cells.…”
Section: Introductionmentioning
confidence: 99%